Pengembangan LKPD Berbasis Proyek Eco Printing Untuk Pengenalan Morfologi Daun - Rinarti; Mahwar Qurbaniah; Anandita Eka Setiadi (Qalam : Jurnal Ilmu Kependidikan, 2024)
Teachers at SMA Negeri 1 Subah need LKPD to support the project. The purpose of the study was to determine the response and feasibility of LKPD by using an eco print project for the introduction of leaf morphology for grade X science students as a learning medium at SMA Negeri 1 Subah. Thedevelopment of LKPD asa learning medium uses the R&D method based on the Allesi and Trolip models. The three phases of the research phase are development, design, and planning. Likert scale questionnaires are used as data collection tools. Data were collected using three techniques: interviews, questionnaires, and observations. Descriptive data analysis. Research findings show that eco-printing project-based LKPD learning consistently meets high standards of media quality (92.4%), language quality (88%), and material quality (96.7%). Students responded to LKPD with great strength (83.29) according to the beta test results.. We can conclude that the Student Worksheet (LKPD) based on the eco printing project is feasible to use and has received a very strong response as a learning medium for the introduction of leaf morphology in plant material.   Keywords : Eco Printing, LKPD,  Leaf Morphology